Graphene transfer in vacuum yielding a high quality graphene. (November 2015) - Lee, Sangchul; Lee, Sang Kyung; Kang, Chang Goo; Cho, Chunhum; Lee, Young Gon; Jung, Ukjin; Lee, Byoung Hun
Abstract: The importance of proper graphene transfer process cannot be emphasized more because it is so closely related to the performance and stability of graphene devices. In this work, a new transfer method utilizing a voluntary bonding of a graphene film to a target substrate in vacuum is demonstrated. The problems originated from water and air molecules which prevent a robust bonding and degrade the electrical characteristics could be drastically alleviated. As a result, graphene field-effect transistors showed nearly symmetric I d – V g characteristics with a minimal hysteresis and drastically improved device stability in air for more than a month could be obtained.